Flaky high-entropy sulfide, preparation method and application thereof, and kanamycin concentration detection method

By preparing sine-like high-entropy sulfide (CDZNCOAGIN) XS and introduce Fey nanobine-adaptable body systems, the problems of expensive equipment and insufficient sensitivity in the detection method of Kenamycin have achieved high sensitivity and high selective testing. The detection limit is as low as 0.15pg ml-1.

CN119370899APending Publication Date: 2025-01-28ZHEJIANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411503620.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, the kanamycin detection method has problems such as expensive equipment, insufficient sensitivity or selectivity, and complex operation, which limits its application in rapid detection. The photoactivity stability of high entropy sulfides is low, which limits its wide application in photoelectric applications.

Method used

Use solvents thermal system of chip-shaped high entropy sulfide (CDZNCOAGIN) XS, and by introducing fey nanobine-adaptation system to generate supersonic free radicals and hydroxyl free radicals, dopamine oxygen is dopamine, adhesive to high entropy to high entropy to high entropy to high entropy to high entropy The surface of the material is to switch the cathode photovoltaic signal to build a ratio sensor used for Kenithromycin detection.

Benefits of technology

A high sensitivity detection of Kanamycin is achieved, the detection limit is as low as 0.15pg ML-1, and the sensor has good stability and linear response characteristics, which improves the accuracy of the detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370899A_ABST
    Figure CN119370899A_ABST
Patent Text Reader

Abstract

The invention provides a flaky high-entropy sulfide, a preparation method and application thereof, and a kanamycin concentration detection method. The flaky high-entropy sulfide is prepared by adopting a simple solvothermal method and has excellent PEC response, superoxide free radicals and hydroxyl free radicals can be generated by introducing the FeY nano enzyme-aptamer to oxidize dopamine into polydopamine, and the polydopamine is adhered to the surface of the flaky high-entropy sulfide so as to switch a cathode photoelectric signal; the sensor for kanamycin detection is successfully constructed; the high-entropy sulfide has better photochemical activity due to the synergistic effect generated among the five metals, meanwhile, the sensor prepared from the high-entropy sulfide has good stability and linear response characteristics based on polarity conversion caused by free radical induced PDA adhesion, and the detection accuracy is improved. According to the method, kanamycin can be sensitively detected in a range of 0.001-10ng mL <-1 >, and the detection limit is as low as 0.15 pg mL <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of kanamycin concentration detection, and in particular to a flaky high entropy sulfide, a preparation method and application thereof, and a kanamycin concentration detection method. Background Art

[0002] Kanamycin is a drug used to treat bacterial infections and is effective against a variety of bacteria. However, long-term or high-dose use can cause ototoxicity and nephrotoxicity to the human body, and may cause serious side effects such as hearing loss and renal failure. In nature, kanamycin enters water bodies and soil through medical wastewater and agricultural discharges and is not easily degraded. It may not only promote bacterial resistance, but also disrupt the balance of microorganisms in the ecosystem, affect biodiversity, and ultimately endanger the health of animals and humans through the food chain.

[0003] At present, the technologies for detecting kanamycin mainly include high performance liquid chromatography, gas chromatography, enzyme-linked immunosorbent assay and mass spectrometry. Although the above methods can detect kanamycin, they each have problems such as expensive equipment, insufficient sensitivity or selectivity, and complex operation, which limit their application in rapid detection. In contrast, the high entropy-based PEC detection technology can become a powerful tool for rapid detection of kanamycin because of its simplicity, rapidity and high cost-effectiveness. However, the photoactivity of high entropy sulfides often limits the widespread application of this technology, which is a technical bottleneck that needs to be overcome urgently.

[0004] High-entropy alloys (HEAs) are a class of alloys composed of five or more elements, and the molar fraction of each element is roughly equal. Unlike traditional alloys, high-entropy sulfides have shown great potential in optoelectronic properties, especially adjustable band gap, good thermal stability, and high carrier mobility, which make them have broad application prospects in photovoltaics, photocatalysis, photodetectors and other fields. Although the multi-element combination of high-entropy sulfides provides an adjustable electronic structure, this complexity also makes the optimization of optoelectronic properties such as electronic band gap and carrier mobility challenging, and its photoactive stability is low. Therefore, finding an ideal combination for optoelectronic applications requires a lot of experiments and optimization work. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of low stability of traditional photoactive materials and to propose a flaky high entropy sulfide and a preparation method and application thereof, and a kanamycin detection method.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a flaky high entropy sulfide, comprising the following steps:

[0008] Dissolving Cd salt, Zn salt, Co salt, Ag salt, In salt and thioacetamide in water to obtain a mixture;

[0009] placing the mixture in a reactor to react, and separating to obtain a precipitate;

[0010] The precipitate is washed and dried to obtain flaky high entropy sulfide.

[0011] Preferably, the Cd salt includes at least one of Cd(CH3COO)2, CdCl2, and Cd(NO3)2;

[0012] And / or, the Zn salt includes at least one of Zn(CH3COO)2, Zn(NO3)2, ZnSO4, and ZnCl2;

[0013] And / or, the Co salt includes at least one of Co(CH3COO)2, Co(NO3)2, CoSO4, and CoCl2;

[0014] And / or, the Ag salt includes at least one of AgCH3COO and AgNO3;

[0015] And / or, the In salt includes at least one of In(NO3)3, InCl3, In2(SO4)3, and In(CH3COO)3;

[0016] And / or, the molar ratio of the Cd salt, Zn salt, Co salt, Ag salt, In salt and thioacetamide is (1-1.2):(1-1.2):(1-1.2):(1-1.2):(1-1.2):(1-1.2);

[0017] The molar volume ratio of the Co salt to the water is (1-1.2) mmol: (35-40) mL;

[0018] And / or, the reaction temperature is 180-190° C., and the reaction time is 12-15 hours.

[0019] In a second aspect, the present invention further provides a flaky high entropy sulfide prepared by the preparation method.

[0020] In a third aspect, the present invention also provides a method for preparing a nanozyme, comprising the following steps:

[0021] Dissolve Zn salt and 2-methylimidazole in methanol respectively, mix and stir, let stand, and separate to obtain a precipitate;

[0022] The precipitate, Fe salt and Y salt are added into methanol, heated and evaporated to dryness, and the nanomaterial is separated;

[0023] calcining the nanomaterial under an inert atmosphere to obtain a calcined product;

[0024] The calcined product is dissolved in dilute sulfuric acid and etched to separate the nanozyme.

[0025] Preferably, the Fe salt is Fe(ACAC)3;

[0026] And / or, the Y salt is Y(ACAC)3;

[0027] And / or, the Zn salt includes at least one of Zn(CH3COO)2, Zn(NO3)2, ZnSO4, and ZnCl2;

[0028] and / or, dissolving Zn salt and 2-methylimidazole in methanol respectively, stirring at 20-25° C. for 10-20 min, standing for 12-15 h, washing with methanol and separating to obtain a precipitate; wherein the molar ratio of Zn salt to 2-methylimidazole is (0.04-0.05):(0.16-0.20), and the molar volume ratio of Zn salt to methanol is (0.04-0.05) mol:(200-400) mL;

[0029] And / or, adding the precipitate and the Fe salt and the Y salt to methanol, heating at 80-90° C. to evaporate the methanol, and separating to obtain the nanomaterial; wherein the mass ratio of the precipitate to the Fe salt and the Y salt is (1-1.2):(0.025-0.03):(0.025-0.03), and the mass volume ratio of the Fe salt to the methanol is (0.025-0.03) g:(50-100) mL;

[0030] And / or, calcining the nanomaterial under an inert atmosphere to obtain a calcined product, specifically comprising: heating the nanomaterial under an inert atmosphere from room temperature to 800-900° C. at a rate of 5-6° C. / min, calcining for 2-3 hours, and then cooling to room temperature to obtain a calcined product;

[0031] The inert atmosphere includes at least one of nitrogen, helium, neon and argon;

[0032] And / or, in the step of dissolving the calcined product in dilute sulfuric acid for etching, the etching comprises: placing the calcined product in dilute sulfuric acid, etching at 20-25° C. for 10-15 hours, and the concentration of the dilute sulfuric acid is 0.5-1M.

[0033] In a fourth aspect, the present invention also provides a flaky high entropy sulfide prepared by the preparation method or the use of the flaky high entropy sulfide in detecting the concentration of kanamycin.

[0034] In a fifth aspect, the present invention further provides a biosensor, wherein the method for constructing the biosensor comprises the following steps:

[0035] S1, coating the flaky high entropy sulfide on the surface of the electrode and drying to form a modified electrode;

[0036] S2, dropping polymethacrylate sodium salt solution on the surface of the modified electrode, incubating, and washing the electrode with PBS buffer;

[0037] S3, drop the EDC-NHS mixed solution onto the electrode surface in S2, incubate, and wash the electrode with PBS buffer;

[0038] S4, drop the cDNA solution onto the electrode surface in S3, incubate, and wash the electrode with PBS buffer;

[0039] S5, drop the BSA solution onto the electrode surface in S4, incubate, and wash the electrode with PBS buffer;

[0040] S6, adding the aptamer Apt solution dropwise to the electrode surface in S5, incubating, and washing the electrode with PBS buffer;

[0041] S7, dropping the SA-FeY solution onto the electrode surface in S6, incubating, and washing the electrode with PBS buffer to obtain a biosensor;

[0042] Wherein, the gene sequence of the cDNA is 5'-GTCGGCTTAGCCTCAACCCCCA-3';

[0043] The gene sequence of the aptamer Apt is 5'-TGGGGGTTGAGGCTA AGCCGAC-3';

[0044] The preparation method of the SA-FeY solution is:

[0045] Adding the nanozyme prepared by the preparation method into water to obtain a nanozyme solution;

[0046] The streptavidin solution and the nanozyme solution were mixed, the supernatant was removed by centrifugation, and the precipitate was collected; PBS buffer was added to the precipitate to obtain a SA-FeY solution.

[0047] Preferably, the method for constructing the biosensor comprises the following steps:

[0048] S1. Add the flaky high entropy sulfide into water to obtain 3-4 mg mL -1 The flaky high entropy sulfide solution is coated on the electrode surface and dried to form a modified electrode;

[0049] S2, dripping polymethacrylate sodium salt solution onto the surface of the modified electrode, incubating at 36-37°C for 0.5-1h, and washing the electrode with PBS buffer; the mass concentration of the polymethacrylate sodium salt solution is 0.15-0.2%;

[0050] S3, dripping the EDC-NHS mixed solution onto the electrode surface in S2, incubating at 4-5°C for 1-2h, and washing the electrode with PBS buffer; the preparation method of the EDC-NHS mixed solution is as follows: adding EDC and NHS into PBS buffer to obtain an EDC-NHS mixed solution, wherein the concentration of EDC is 10-12mM, and the concentration of NHS is 2-4mM;

[0051] S4, dropping the cDNA solution onto the electrode surface in S3, incubating at 4-5°C for 12-15h, and washing the electrode with PBS buffer; the preparation method of the cDNA solution is: adding cDNA to PBS buffer to obtain a cDNA solution, wherein the concentration of the cDNA solution is 1.0-1.2 μM;

[0052] S5, dropping a BSA solution onto the electrode surface in S4, incubating at 4-5°C for 1-2 hours, and washing the electrode with a PBS buffer solution; the BSA solution is prepared by adding BSA to a PBS buffer solution to obtain a BSA solution; the mass concentration of the BSA solution is 1.0-2.0%;

[0053] S6, adding the aptamer Apt solution dropwise to the electrode surface in S5, incubating at 36-37° C. for 1-2 hours, and washing the electrode with PBS buffer; the preparation method of the aptamer Apt solution is: adding the aptamer Apt to the PBS buffer to obtain the aptamer Apt solution, wherein the concentration of the aptamer Apt solution is 1.0-1.2 μM;

[0054] S7, dropping the SA-FeY solution onto the electrode surface in S6, incubating at 36-37°C for 1-2h, and washing the electrode with PBS buffer to obtain a biosensor;

[0055] The concentration of the streptavidin solution is 1 to 2 mg / mL, and the concentration of the nanozyme solution is 1 to 2 mg / mL;

[0056] The streptavidin solution and the nanozyme solution are mixed, the supernatant is removed by centrifugation, and the precipitate is collected; in the step of adding PBS buffer to the precipitate, the volume ratio of the streptavidin solution, the nanozyme solution, and the PBS buffer solution is (200-220):(400-420):(600-620);

[0057] The pH of the PBS buffer is 7.4-7.5.

[0058] In a sixth aspect, the present invention further provides a method for detecting kanamycin concentration, comprising the following steps:

[0059] S1. Provide the biosensor, drop a kanamycin test solution onto the electrode surface of the biosensor, incubate at 36-37° C. for 1-2 h, and wash the electrode with PBS buffer;

[0060] S2, placing the electrode in a Tris-HCl buffer containing ascorbic acid, and detecting the anode photoresponse current signal of the electrode when the concentration of natamycin is zero and at the current concentration;

[0061] The anode light response current signal value of the electrode at the current concentration is subtracted from the anode light response current signal value of the electrode when the napromycin concentration is zero, to obtain the anode light response current signal difference;

[0062] S3, add dopamine solution to the electrode surface in S2, incubate at 36-37°C for 0.5-1h, and wash the electrode with PBS buffer;

[0063] S4, placing the electrode in S3 in a Tris-HCl buffer containing ascorbic acid, and detecting the cathode photoresponse current signal of the electrode when the concentration of natamycin is zero and at the current concentration;

[0064] The cathode light response current signal value of the electrode at the current concentration is subtracted from the cathode light response current signal value of the electrode when the namycin concentration is zero, to obtain the cathode light response current signal difference;

[0065] S5. Detect the kanamycin concentration according to the ratio of the difference of the anode light response current signal to the cathode light response current signal.

[0066] Preferably, the pH of the Tris-HCl buffer is 7.4-7.5, and the concentration of ascorbic acid in the Tris-HCl buffer is 0.1-0.2 M;

[0067] The dopamine solution is prepared by adding dopamine into water to obtain the dopamine solution; the concentration of the dopamine solution is 500-600 mM.

[0068] The flaky high entropy sulfide, preparation method and application thereof, and kanamycin detection method of the present invention have the following beneficial effects compared with the prior art:

[0069] The present invention adopts a simple solvothermal method to prepare (CdZnCoAgIn) xS sheet high entropy sulfide, which has excellent PEC response, can produce superoxide radicals and hydroxyl radicals by introducing FeY nanozyme-aptamer to oxidize dopamine (DA) to polydopamine (PDA), and adhere to the surface of sheet high entropy sulfide to switch the cathode photoelectric signal, and successfully construct a ratio sensor for kanamycin detection; due to the synergistic effect between the five metals, the sheet high entropy sulfide has better photochemical activity, and the polarity conversion caused by free radical-induced PDA adhesion makes the PEC sensor prepared by sheet high entropy sulfide have good stability and linear response characteristics, and improves the detection accuracy. This method can be used in 0.001-10ng mL -1 The detection limit of kanamycin was as low as 0.15 pg mL -1 When further applied to the determination of kanamycin concentration in the environment, this method obtained satisfactory results, demonstrating its broad potential in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0071] Figure 1 The flaky high entropy sulfide (CdZnCoAgIn) prepared by the present invention x Schematic diagram of the S-type detection of kanamycin;

[0072] Figure 2 The flaky high entropy sulfide (CdZnCoAgIn) prepared in step S3 of Example 1 x Structural characterization of S;

[0073] Figure 3 The flaky high entropy sulfide (CdZnCoAgIn) prepared in Example 1 x S PEC signal measured in Tris-HCl buffer (pH = 7.4) containing ascorbic acid (AA);

[0074] Figure 4 The flaky high entropy sulfide (CdZnCoAgIn) prepared in step S3 of Example 1 x XRD pattern of S;

[0075] Figure 5 The flaky high entropy sulfide (CdZnCoAgIn) prepared in step S3 of Example 1 xXPS spectrum of S;

[0076] Figure 6 The structure characterization of the FeY nanozyme prepared in Example 2;

[0077] Figure 7 are a-ZnS, b-(ZnCd)xS, c-(ZnCdAg)xS, c-(ZnCdAgIn) x S, c-(CdZnCoAgIn) x S PEC signals of these five materials;

[0078] Figure 8 Schematic diagram of the proposed PEC response sensing analysis and the corresponding EIS characterization diagram during the step-by-step construction process;

[0079] Fig. 9 This is a photoelectrochemical sensing analysis diagram of kanamycin;

[0080] Fig.10 A comparison chart of selectivity for detecting kanamycin and a schematic diagram of sensor stability;

[0081] Fig.11 The flaky high entropy sulfide (CdZnCoAgIn) in Example 1 x Schematic diagram of the reproducibility of the PEC response of S. DETAILED DESCRIPTION

[0082] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0083] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0084] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any quoted numbers (fractions or integers) within the indicated range.

[0085] The present invention provides a method for preparing a flaky high entropy sulfide, comprising the following steps:

[0086] S1. Dissolving Cd salt, Zn salt, Co salt, Ag salt, In salt and thioacetamide in water to obtain a mixture;

[0087] S2, placing the mixture in a reactor for reaction, and separating to obtain a precipitate;

[0088] S3. Wash and dry the precipitate to obtain flaky high entropy sulfide.

[0089] In some embodiments, the Cd salt includes at least one of Cd(CH3COO)2, CdCl2, and Cd(NO3)2.

[0090] In some embodiments, the Zn salt includes at least one of Zn(CH3COO)2, Zn(NO3)2, ZnSO4, and ZnCl2.

[0091] In some embodiments, the Co salt includes at least one of Co(CH3COO)2, Co(NO3)2, CoSO4, and CoCl2.

[0092] In some embodiments, the Ag salt includes at least one of AgCH3COO, AgNO3.

[0093] In some embodiments, the In salt includes at least one of In(NO3)3, InCl3, In2(SO4)3, and In(CH3COO)3.

[0094] In some embodiments, the molar ratio of Cd salt, Zn salt, Co salt, Ag salt, In salt and thioacetamide is (1-1.2):(1-1.2):(1-1.2):(1-1.2):(1-1.2):(1-1.2).

[0095] The molar volume ratio of the Co salt to the water is (1-1.2) mmol: (35-40) mL;

[0096] In some embodiments, the reaction temperature is 180-190° C., and the reaction time is 12-15 h.

[0097] In some embodiments, Cd salt, Zn salt, Co salt, Ag salt, In salt and thioacetamide are dissolved in water at a molar ratio of 1:1:1:1:1:1, the molar volume ratio of Co salt and water is 1 mmol:35 mL, and ultrasonic treatment is performed for 20 min; the mixture is placed in a 50 mL reactor and reacted at 180 ° C for 12 h, and then cooled to room temperature and separated to obtain a precipitate; the precipitate is washed 3 times with pure water and 3 times with ethanol, and dried in an oven at 60 ° C overnight to obtain a pure flaky high entropy sulfide material.

[0098] Based on the same inventive concept, the present invention also provides a flaky high entropy sulfide, which is prepared by the above-mentioned preparation method.

[0099] Based on the same inventive concept, the present invention also provides a method for preparing a nanozyme, comprising the following steps:

[0100] S1. Dissolve Zn salt and 2-methylimidazole in methanol respectively, mix and stir, let stand, and separate to obtain a precipitate;

[0101] S2, adding the precipitate, Fe salt and Y salt into methanol, heating and evaporating to dryness, and separating to obtain the nanomaterial;

[0102] S3, calcining the nanomaterial under an inert atmosphere to obtain a calcined product;

[0103] S4. The calcined product is dissolved in dilute sulfuric acid and etched to separate the nanozyme.

[0104] In some embodiments, the Fe salt is Fe(ACAC)3 (ferric triacetylacetonate).

[0105] In some embodiments, the Y salt is Y(ACAC)3 (yttrium(III) acetylacetonate).

[0106] In some embodiments, the Zn salt includes at least one of Zn(CH3COO)2, Zn(NO3)2, ZnSO4, and ZnCl2.

[0107] In some embodiments, Zn salt and 2-methylimidazole are respectively dissolved in methanol, stirred at 20-25°C for 10-20 min, allowed to stand for 12-15 h, washed with methanol and separated to obtain a precipitate; wherein the molar ratio of Zn salt to 2-methylimidazole is (0.04-0.05):(0.16-0.20), and the molar volume ratio of Zn salt to methanol is (0.04-0.05) mol:(200-400) mL.

[0108] In some embodiments, the precipitate and Fe salt and Y salt are added to methanol, the methanol is evaporated at 80-90°C, and the nanomaterial is separated; wherein the mass ratio of the precipitate to the Fe salt and Y salt is (1-1.2):(0.025-0.03):(0.025-0.03), and the mass volume ratio of the Fe salt to the methanol is (0.025-0.03) g:(50-100) mL.

[0109] In some embodiments, the nanomaterial is calcined under an inert atmosphere to obtain a calcined product, specifically comprising: heating the nanomaterial from room temperature to 800-900° C. at a rate of 5-6° C. / min under an inert atmosphere, calcining for 2-3 hours, and then cooling to room temperature to obtain a calcined product;

[0110] The inert atmosphere includes at least one of nitrogen, helium, neon and argon;

[0111] In some embodiments, in the step of dissolving the calcined product in dilute sulfuric acid for etching, the etching comprises: placing the calcined product in dilute sulfuric acid, etching at 20-25° C. for 10-15 hours, and the concentration of the dilute sulfuric acid is 0.5-1M.

[0112] Based on the same inventive concept, the present invention also provides a flaky high entropy sulfide prepared by the above preparation method or the use of the above flaky high entropy sulfide in detecting the concentration of kanamycin.

[0113] Based on the same inventive concept, the present invention also provides a biosensor, the construction method of which comprises the following steps:

[0114] S1, coating the flaky high entropy sulfide on the electrode surface and drying to form a modified electrode;

[0115] S2, dropping polymethacrylate sodium salt solution on the surface of the modified electrode, incubating, and washing the electrode with PBS buffer;

[0116] S3, drop the EDC-NHS mixed solution onto the electrode surface in S2, incubate, and wash the electrode with PBS buffer;

[0117] S4, drop the cDNA solution onto the electrode surface in S3, incubate, and wash the electrode with PBS buffer;

[0118] S5, drop the BSA solution onto the electrode surface in S4, incubate, and wash the electrode with PBS buffer;

[0119] S6, adding the aptamer Apt solution dropwise to the electrode surface in S5, incubating, and washing the electrode with PBS buffer;

[0120] S7. Add the SA-FeY solution dropwise onto the electrode surface in S6, incubate, and wash the electrode with PBS buffer to obtain a biosensor.

[0121] In some embodiments, the gene sequence of the cDNA is 5'-GTCGGCTTAGCCTCAACCCCCA-3', as shown in SEQ ID NO:1.

[0122] In some embodiments, the gene sequence of the aptamer Apt is 5′-TGGGGGTTGAGGCTA AGCCGAC-3′, as shown in SEQ ID NO:2.

[0123] In some embodiments, the SA-FeY solution is prepared by:

[0124] Adding the nanozyme prepared by the above preparation method into water to obtain a nanozyme solution;

[0125] The streptavidin solution and the nanozyme solution were mixed, the supernatant was removed by centrifugation, and the precipitate was collected; PBS buffer was added to the precipitate to obtain a SA-FeY solution.

[0126] In some embodiments, the method for constructing a biosensor comprises the following steps:

[0127] S1. Add the above-mentioned flaky high entropy sulfide into water to obtain 3-4 mg mL -1 The flaky high entropy sulfide solution is coated on the electrode surface and dried to form a modified electrode;

[0128] S2, dripping polymethacrylate sodium salt solution (PAA) on the surface of the modified electrode, incubating at 36-37°C for 0.5-1h, and washing the electrode with PBS buffer; the mass concentration of polymethacrylate sodium salt solution is 0.15-0.2%;

[0129] S3, dripping the EDC-NHS mixed solution onto the electrode surface in S2, incubating at 4-5°C for 1-2h, and washing the electrode with PBS buffer; the preparation method of the EDC-NHS mixed solution is as follows: adding EDC and NHS into PBS buffer to obtain an EDC-NHS mixed solution, wherein the concentration of EDC is 10-12mM, and the concentration of NHS is 2-4mM;

[0130] S4, dropping the cDNA solution onto the electrode surface in S3, incubating at 4-5°C for 12-15h, and washing the electrode with PBS buffer; the preparation method of the cDNA solution is: adding cDNA to PBS buffer to obtain a cDNA solution, wherein the concentration of the cDNA solution is 1.0-1.2 μM;

[0131] S5, dropping a BSA solution onto the electrode surface in S4, incubating at 4-5°C for 1-2 hours, and washing the electrode with a PBS buffer solution; the BSA solution is prepared by adding BSA to a PBS buffer solution to obtain a BSA solution; the mass concentration of the BSA solution is 1.0-2.0%;

[0132] S6, adding the aptamer Apt solution dropwise to the electrode surface in S5, incubating at 36-37° C. for 1-2 hours, and washing the electrode with PBS buffer; the preparation method of the aptamer Apt solution is as follows: adding the aptamer Apt to the PBS buffer to obtain the aptamer Apt solution, wherein the concentration of the aptamer Apt solution is 1.0-1.2 μM;

[0133] S7. Add the SA-FeY solution dropwise to the electrode surface in S6, incubate at 36-37° C. for 1-2 h, and wash the electrode with PBS buffer to obtain a biosensor.

[0134] In some implementations, the concentration of the streptavidin solution is 1 to 2 mg / mL, and the concentration of the nanozyme solution is 1 to 2 mg / mL;

[0135] The streptavidin solution and the nanozyme solution are mixed, the supernatant is removed by centrifugation, and the precipitate is collected; in the step of adding PBS buffer to the precipitate, the volume ratio of the streptavidin solution, the nanozyme solution, and the PBS buffer solution is (200-220):(400-420):(600-620);

[0136] The pH of PBS buffer is 7.4-7.5.

[0137] In some embodiments, the electrode is a FTO electrode, an ITO electrode, or the like.

[0138] In the above embodiment, EDC is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, NHS is N-hydroxysuccinimide, and the streptavidin solution is prepared by adding streptavidin to PBS buffer to obtain a streptavidin solution.

[0139] In some embodiments, the polymethacrylate sodium salt solution is also called sodium polymethacrylate, sodium polyacrylate, and polyacrylic acid sodium salt.

[0140] In some embodiments, the drop volume of the flaky high entropy sulfide solution, the polymethacrylate sodium salt solution, the EDC-NHS mixed solution, the cDNA solution, the BSA solution, the aptamer Apt solution, and the SA-FeY solution is 20-30 μL.

[0141] The biosensor constructed by the present invention can be used to detect the concentration of kanamycin in the range of 0.001-10 ng mL -1 The detection limit of kanamycin was as low as 0.15 pg mL -1 Meanwhile, the sensor exhibited good selectivity for kanamycin.

[0142] Based on the same inventive concept, the present invention also provides a method for detecting kanamycin concentration, comprising the following steps:

[0143] S1. Provide the above-mentioned biosensor, drop a kanamycin test solution onto the electrode surface of the biosensor, incubate at 36-37° C. for 1-2 h, and wash the electrode with PBS buffer;

[0144] S2, placing the electrode in a Tris-HCl buffer containing ascorbic acid, and detecting the anode photoresponse current signal of the electrode when the concentration of natamycin is zero and at the current concentration;

[0145] The anode light response current signal value of the electrode at the current concentration is subtracted from the anode light response current signal value of the electrode when the napromycin concentration is zero, to obtain the anode light response current signal difference;

[0146] S3, add dopamine (DA) solution to the electrode surface in S2, incubate at 36-37°C for 0.5-1h, and wash the electrode with PBS buffer;

[0147] S4, placing the electrode in S3 in a Tris-HCl buffer containing ascorbic acid (AA), and detecting the cathode photoresponse current signal of the electrode when the concentration of natamycin is zero and at the current concentration;

[0148] The cathode light response current signal value of the electrode at the current concentration is subtracted from the cathode light response current signal value of the electrode when the namycin concentration is zero, to obtain the cathode light response current signal difference;

[0149] S5. Detect the kanamycin concentration according to the ratio of the difference of the anode light response current signal to the cathode light response current signal.

[0150] In some embodiments, the pH of the Tris-HCl buffer is 7.4-7.5, and the concentration of ascorbic acid in the Tris-HCl buffer is 0.1-0.2 M;

[0151] In some embodiments, the dopamine solution is prepared by adding dopamine into water to obtain the dopamine solution; the concentration of the dopamine solution is 500-600 mM.

[0152] Specifically, in the above embodiment, the electrode is placed in a Tris-HCl buffer containing ascorbic acid, and the anode photoresponse current signal of the electrode is detected when the kanamycin concentration is zero and at the current concentration, respectively. The meaning is: when the kanamycin concentration in the kanamycin test solution is zero, the kanamycin test solution (the kanamycin concentration is zero) is added to the electrode surface of the biosensor, incubated at 36-37°C for 1-2h, and the electrode is washed with PBS buffer; the electrode is placed in a Tris-HCl buffer containing ascorbic acid, and the kanamycin concentration is detected when it is zero. The anode light response current signal I1 of the biosensor is obtained; if the concentration of kanamycin in the kanamycin test solution is not zero, that is, the test solution contains a certain concentration of kanamycin, the kanamycin test solution (the test solution contains a certain concentration of kanamycin) is added to the electrode surface of the biosensor, incubated at 36-37°C for 1-2h, and the electrode is washed with PBS buffer; the electrode is placed in a Tris-HCl buffer containing ascorbic acid, and the anode light response current signal I2 of the biosensor is detected at the kanamycin concentration; the difference in the anode light response current signal is ΔI A =I2-I1.

[0153] The electrode in S3 is placed in a Tris-HCl buffer containing ascorbic acid (AA), and the cathode light response current signal of the electrode is detected when the kanamycin concentration is zero and at the current concentration, respectively. The meaning is: when the kanamycin concentration in the kanamycin test solution is zero, the electrode in S3 is placed in a Tris-HCl buffer containing ascorbic acid (AA), and the test solution does not contain kanamycin at this time. When the kanamycin concentration is zero, the cathode light response current signal I3 of the biosensor is detected; if the kanamycin concentration in the kanamycin test solution is not zero, that is, the test solution contains a certain concentration of kanamycin, the electrode in S3 is placed in a Tris-HCl buffer containing ascorbic acid (AA), and the test solution contains a certain concentration of kanamycin at this concentration. At this concentration, the cathode light response current signal I4 of the biosensor is detected; the difference in the cathode light response current signal is ΔI k =I4-I3; the ratio of the difference between the anode light response current signal and the cathode light response current signal is ΔI A / ΔI k The ratio was used to detect the concentration of kanamycin.

[0154] Specifically, in the above embodiment, the electrode is placed in a Tris-HCl buffer containing ascorbic acid (AA) to form a three-electrode system, the Tris-HCl buffer containing ascorbic acid (AA) is used as the electrolyte, the platinum electrode is used as the counter electrode, the silver-silver chloride electrode is used as the reference electrode, the modified electrode in the above biosensor is used as the working electrode, and an electrochemical workstation is used. The xenon lamp is irradiated for 10 seconds, turned off for 10 seconds, and a cycle of 20 seconds is performed for 400 seconds to detect the light response current signal of the electrode.

[0155] In some embodiments, a flaky high entropy sulfide or the flaky high entropy sulfide is coated on the surface of an electrode, and PAA, NHS / EDC, cDNA, BSA, aptamer Apt, SA-FeY solution and kanamycin solutions of different concentrations are sequentially dripped on for incubation, and washed with PBS solution after each incubation; the electrode is placed in a Tris-HCl buffer containing ascorbic acid (AA) for detection to obtain anodic PEC signals of different intensities; DA is dripped on the incubated electrode again to switch the cathode PEC signal; and the kanamycin concentration is detected according to the ratio of the anode signal difference to the cathode signal difference.

[0156] The principle of the kanamycin concentration detection method of the present invention is as follows: Figure 1 As shown, the flake high entropy sulfide (CdZnCoAgIn) x S has a good PEC response. By introducing FeY nanozyme-aptamer, it can produce superoxide radicals and hydroxyl radicals to oxidize dopamine (DA) to polydopamine (PDA), and adhere to the surface of flaky high-entropy sulfide, thereby switching the cathode signal. A ratiometric sensor for kanamycin detection was successfully constructed, achieving high-sensitivity and high-selectivity detection of kanamycin (KAN).

[0157] The present invention adopts the solvothermal method to prepare the flaky high entropy sulfide (CdZnCoAgIn) x S, the sheet-like high entropy sulfide has a good PEC response. By introducing FeY nanozyme-aptamer, superoxide radicals and hydroxyl radicals can be generated to oxidize dopamine (DA) to polydopamine (PDA) and adhere to the surface of the high entropy material, resulting in switching of the cathode signal. A ratio sensor for kanamycin detection was successfully constructed; due to the synergistic effect between the five metals, the sheet-like high entropy sulfide has better photoelectrochemical activity. At the same time, based on the polarity conversion caused by free radical-induced PDA adhesion, the PEC sensor prepared by the sheet-like high entropy sulfide shows excellent stability and linear response characteristics, further improving the accuracy of detection. Through PEC response, this method can be used in the range of 0.001-10ng mL -1 The detection limit of kanamycin was as low as 0.15 pg mL -1When further applied to the determination of kanamycin concentration in the environment, this method obtained satisfactory results, demonstrating its broad potential in practical applications.

[0158] The following further describes the flaky high entropy sulfide of the present application and its preparation method and application, and the kanamycin concentration detection method with specific examples. This section further describes the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0159] The following further describes the flaky high entropy sulfide of the present application and its preparation method and application, and the kanamycin concentration detection method with specific examples. This section further describes the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0160] In the following examples, the polymethacrylate sodium salt solution was prepared by adding water to a commercially available polymethacrylate sodium salt solution (purchased from Sigma-Aldrich, product number 434507) to prepare a polymethacrylate sodium salt solution with a mass concentration of 0.15 wt %.

[0161] Example 1

[0162] The present invention provides a method for preparing a flaky high entropy sulfide, comprising the following steps:

[0163] S1. Dissolve Cd salt, Zn salt, Co salt, Ag salt, In salt and thioacetamide in water, and perform ultrasound treatment for 20 min to obtain a mixture; wherein the molar ratio of Cd salt, Zn salt, Co salt, Ag salt, In salt and thioacetamide is 1:1:1:1:1:1; the molar volume ratio of Co salt and water is 1 mmol:35 mL; the Cd salt is Cd(CH3COO)3·2H2O, the Zn salt is Zn(CH3COO)2·2H2O, the Co salt is Co(CH3COO)2·4H2O, the Ag salt is AgCH3COO, and the In salt is In(NO3)3;

[0164] S2, placing the mixture in a 50 mL reactor at 180° C. for 12 h, cooling to room temperature, and separating to obtain a precipitate;

[0165] S3. Wash the precipitate with pure water three times, with ethanol three times, and dry it in an oven at 60° C. overnight to obtain a pure flaky high-entropy sulfide material.

[0166] Example 2

[0167] This embodiment provides a method for preparing a nanozyme, comprising the following steps:

[0168] S1. Dissolve Zn(CH3COO)2 and 2-methylimidazole in methanol respectively, stir for 10 min at room temperature (25°C) and let stand for 12 h, wash with methanol and separate to obtain a precipitate; wherein the molar ratio of Zn(CH3COO)2 and 2-methylimidazole is 0.04:0.16, and the molar volume ratio of Zn(CH3COO)2 and methanol is 0.04 mol:375 mL;

[0169] S2, adding the precipitate and Fe(ACAC)3 (iron triacetylacetonate) and Y(ACAC)3 (yttrium (III) acetylacetonate) into methanol, stirring and evaporating the methanol at 80°C, and drying to obtain the nanomaterial; the mass ratio of the precipitate to Fe(ACAC)3 and Y(ACAC)3 is 1:0.025:0.025, and the mass volume ratio of Fe(ACAC)3 to methanol is 0.025g:50mL;

[0170] S3, heating the nanomaterial from room temperature to 800° C. at a rate of 5° C. / min under a nitrogen atmosphere, calcining for 2 h, and then cooling to room temperature to obtain a calcined product;

[0171] S4. The calcined product is placed in dilute sulfuric acid and etched at 25°C for 12 hours with a dilute sulfuric acid concentration of 0.5 M to separate and obtain FeY nanozyme.

[0172] Example 3

[0173] This embodiment provides a method for constructing a biosensor, comprising the following steps:

[0174] S1. Add the flaky high entropy sulfide prepared in Example 1 into water to obtain 3 mg mL -1 20 μL of the flake high entropy sulfide solution is coated on the surface of the electrode (ITO electrode) and dried to form a modified electrode;

[0175] S2, 20 μL of polymethacrylate sodium salt solution (PAA, 0.15 wt%) was added dropwise onto the surface of the modified electrode, incubated at 37°C for 0.5 h, and the electrode was washed with PBS buffer (pH = 7.4); the mass concentration of polymethacrylate sodium salt solution was 0.15%;

[0176] S3, drip 20 μL of EDC-NHS mixed solution onto the electrode surface in S2, incubate at 4°C for 1 hour, and wash the electrode with PBS buffer (pH=7.4); the preparation method of EDC-NHS mixed solution is as follows: add EDC and NHS into PBS buffer (pH=7.4) to obtain EDC-NHS mixed solution, wherein the concentration of EDC is 10 mM and the concentration of NHS is 2 mM;

[0177] S4, dripping 20 μL of cDNA solution onto the electrode surface in S3, incubating at 4°C for 12 h, and washing the electrode with PBS buffer (pH=7.4); the preparation method of cDNA solution is as follows: adding cDNA into PBS buffer (pH=7.4) to obtain a cDNA solution, the concentration of the cDNA solution is 1.0 μM, and the gene sequence of cDNA is 5'-GTCGGCTTAGCCTCAACCCCCA-3';

[0178] S5, drip 20 μL of BSA solution onto the electrode surface in S4, incubate at 4°C for 1 h, and wash the electrode with PBS buffer (pH=7.4); the preparation method of BSA solution is: add BSA into PBS buffer (pH=7.4) to obtain BSA solution; the mass concentration of BSA solution is 1.0%;

[0179] S6, adding 20 μL of aptamer Apt solution to the electrode surface in S5, incubating at 37° C. for 1 h, and washing the electrode with PBS buffer (pH=7.4); the preparation method of aptamer Apt solution is as follows: adding aptamer Apt to PBS buffer (pH=7.4) to obtain aptamer Apt solution, the concentration of aptamer Apt solution is 1.0 μM, and the gene sequence of aptamer Apt is 5'-TGGGGGTTGAGGCTAAGCCGAC-3';

[0180] S7, adding 20 μL of SA-FeY solution to the electrode surface in S6, incubating at 37°C for 1 h, and washing the electrode with PBS buffer (pH=7.4) to obtain a biosensor;

[0181] The preparation method of SA-FeY solution is:

[0182] The nanozyme prepared in Example 2 is added to water to obtain a nanozyme solution;

[0183] 200 μL of streptavidin solution (SA, 1 mg / mL) was mixed with 400 μL of nanozyme solution (1 mg / mL, solvent: water), shaken overnight at 4°C, centrifuged to remove the supernatant, and the precipitate was collected; 600 μL of PBS buffer (pH = 7.4) was added to the precipitate to obtain SA-FeY solution;

[0184] The streptavidin solution was prepared by adding streptavidin to PBS buffer (pH=7.4) to obtain a streptavidin solution with a concentration of 1 mg / mL;

[0185] The preparation method of the nanozyme solution is as follows: adding the nanozyme solution prepared in Example 2 into water to obtain a nanozyme solution with a concentration of 1 mg / mL.

[0186] Example 4

[0187] This embodiment provides a method for detecting kanamycin concentration, comprising the following steps:

[0188] S1. Provide the biosensor in Example 3, drop 20 μL of kanamycin test solution of different concentrations onto the electrode surface of the biosensor, incubate at 37° C. for 1 h, and wash the electrode with PBS buffer (pH=7.4);

[0189] S2, placing the electrode in a Tris-HCl buffer (pH=7.4) containing ascorbic acid, and detecting the anode photoresponse current signal of the electrode when the kanamycin concentration is zero and at the current concentration;

[0190] The anode light response current signal value of the electrode at the current concentration is subtracted from the anode light response current signal value of the electrode when the napromycin concentration is zero, to obtain the anode light response current signal difference;

[0191] S3, add dopamine (DA) solution to the electrode surface in S2, incubate at 37°C for 0.5h, and wash the electrode with PBS buffer (pH=7.4);

[0192] S4, placing the electrode in S3 in a Tris-HCl buffer (pH=7.4) containing ascorbic acid (AA), and detecting the cathode photoresponse current signal of the electrode when the concentration of natamycin is zero and at the current concentration;

[0193] The cathode light response current signal value of the electrode at the current concentration is subtracted from the cathode light response current signal value of the electrode when the namycin concentration is zero, to obtain the cathode light response current signal difference;

[0194] S5, detecting the kanamycin concentration according to the ratio of the anode light response current signal difference to the cathode light response current signal difference;

[0195] The concentration of ascorbic acid in Tris-HCl buffer was 0.1 M;

[0196] The method for preparing the dopamine solution is: adding dopamine into water to obtain the dopamine solution; the concentration of the dopamine solution is 500 mM.

[0197] Performance Characterization

[0198] Figure 2 The flaky high entropy sulfide (CdZnCoAgIn) prepared in step S3 of Example 1 x Structural characterization of S;

[0199] Figure 2 A flaky high entropy sulfide (CdZnCoAgIn) prepared in step S3 of Example 1 x SEM image of S.

[0200] Figure 2 Where B and C are the flaky high entropy sulfide (CdZnCoAgIn) prepared in step S3 of Example 1 x TEM image of S.

[0201] Figure 2 DF is the STEM image of the (CdZnCoAgIn)xS flaky high entropy sulfide prepared in step S3 of Example 1;

[0202] Figure 2 G in FIG. 1 is the HAADF-STEM-EDS elemental mapping diagram of the (CdZnCoAgIn)xS flaky high entropy sulfide prepared in step S3 in Example 1.

[0203] from Figure 2 It can be seen from the scanning electron microscope that the high entropy sulfide (CdZnCoAgIn) prepared by the present invention x S is in the form of flakes, Figure 2 The transmission electron microscope image shows that the amorphous flake high entropy sulfide material of (CdZnCoAgIn)xS flake high entropy sulfide was successfully prepared.

[0204] Figure 3 The flaky high entropy sulfide (CdZnCoAgIn) prepared in Example 1 x PEC signal of S measured in Tris-HCl buffer (pH = 7.4) containing ascorbic acid (AA); specifically, the flake high entropy sulfide was prepared as 3 mg mL -1 The solution was coated on the ITO electrode and dried, and placed in Tris-HCl buffer (pH=7.4) containing ascorbic acid (AA) to form a three-electrode system, with Tris-HCl buffer containing 0.1 M ascorbic acid (AA) as the electrolyte, a platinum electrode as the counter electrode, a silver-silver chloride electrode as the reference electrode, and the above-mentioned ITO electrode as the working electrode. An electrochemical workstation was used, and a xenon lamp was irradiated for 10 s, turned off for 10 s, and a cycle of 20 s was performed for 400 s to detect the light response current signal of the electrode.

[0205] from Figure 3It can be seen that the flake high entropy sulfide (CdZnCoAgIn) x The PEC signal measured in Tris-HCl buffer (pH=7.4) containing ascorbic acid (AA) is very stable within 400s. Therefore, the flaky high entropy sulfide (CdZnCoAgIn) of the present invention x S can be used to detect kanamycin solution.

[0206] Figure 4 The flaky high entropy sulfide (CdZnCoAgIn) prepared in step S3 of Example 1 x XRD pattern of S.

[0207] from Figure 4 It can be seen that its diffraction peak is similar to the standard cards of Ag2S, CdS, and ZnS, but due to the doping of various metal elements, its lattice has undergone certain adjustments and distortions, confirming the multi-component characteristics of the material. This confirms that the flake high entropy sulfide (CdZnCoAgIn) x The successful synthesis of S.

[0208] Figure 5 The flaky high entropy sulfide (CdZnCoAgIn) prepared in step S3 of Example 1 x XPS spectrum of S, where A is the XPS spectrum of Ag 3d; B is the XPS spectrum of Cd 3d; C is the XPS spectrum of Co 2p; D is the XPS spectrum of In 3d; E is the XPS spectrum of Zn 2p; and F is the XPS spectrum of S2p.

[0209] XPS analysis revealed the chemical state of each element in the material and its binding energy, and further confirmed its surface chemical state.

[0210] Figure 6 The structure characterization of the FeY nanozyme prepared in Example 2;

[0211] Figure 6 Figure A is the SEM image of FeY nanozyme, Figure BC is the TEM image, Figure D is the spherical aberration image, and Figure E is the HAADF-STEM-EDS element mapping image. Figure D proves that the synthesized nanozyme is a single-atom nanozyme. Figure 6 It can be seen from the scanning electron microscopy and transmission electron microscopy that the FeY nanozyme prepared by the present invention has a dodecahedral structure.

[0212] Figure 7 The following materials were synthesized by a similar method as in Example 1 for comparison: (a) ZnS; (b) (ZnCd) x S; (c)(ZnCdAg) xS; (d)(ZnCdAgIn) x S; (e)(CdZnCoAgIn) x S (prepared according to the method in Example 1).

[0213] The preparation method of ZnS is as follows: S1. Zn salt and thioacetamide are dissolved in water, and ultrasonicated for 20 minutes to obtain a mixture; wherein the molar ratio of Zn salt and thioacetamide is 1:1; the molar volume ratio of Zn salt and water is 1mmol:35mL; the Zn salt is Zn(CH3COO)2·2H2O; S2. The mixture is placed in a 50mL reactor and reacted at 180°C for 12 hours, cooled to room temperature, and separated to obtain a precipitate; S3. The precipitate is washed with pure water 3 times, washed with ethanol 3 times, and dried in an oven at 60°C overnight to obtain ZnS.

[0214] (ZnCd) x The preparation method of S is as follows: S1. Dissolve Cd salt, Zn salt and thioacetamide in water, and perform ultrasonic treatment for 20 minutes to obtain a mixture; wherein the molar ratio of Cd salt, Zn salt and thioacetamide is 1:1:1; the molar volume ratio of Cd salt and water is 1mmol:35mL; Cd salt is Cd(CH3COO)3·2H2O, and Zn salt is Zn(CH3COO)2·2H2O; S2. Place the mixture in a 50mL reactor and react at 180°C for 12h, cool to room temperature, and separate to obtain a precipitate; S3. Wash the precipitate with pure water 3 times, with ethanol 3 times, and dry it in an oven at 60°C overnight to obtain (ZnCd) x S.

[0215] (ZnCdAg) x The preparation method of S is as follows: S1. Dissolve Cd salt, Zn salt, Ag salt and thioacetamide in water, and perform ultrasonic treatment for 20 minutes to obtain a mixture; wherein the molar ratio of Cd salt, Zn salt, Ag salt and thioacetamide is 1:1:1:1; the molar volume ratio of Cd salt and water is 1mmol:35mL; Cd salt is Cd(CH3COO)3·2H2O, Zn salt is Zn(CH3COO)2·2H2O, and Ag salt is AgCH3COO; S2. Place the mixture in a 50mL reactor and react at 180°C for 12h, cool to room temperature, and separate to obtain a precipitate; S3. Wash the precipitate with pure water 3 times, with ethanol 3 times, and dry it in an oven at 60°C overnight to obtain (ZnCdAg) x S.

[0216] (ZnCdAgIn) xThe preparation method of S is as follows: S1. Dissolve Cd salt, Zn salt, Ag salt, In salt and thioacetamide in water, and perform ultrasonic treatment for 20 minutes to obtain a mixture; wherein the molar ratio of Cd salt, Zn salt, Ag salt, In salt and thioacetamide is 1:1:1:1:1; the molar volume ratio of Cd salt and water is 1mmol:35mL; Cd salt is Cd(CH3COO)3·2H2O, Zn salt is Zn(CH3COO)2·2H2O, Ag salt is AgCH3COO, and In salt is In(NO3)3; S2. Place the mixture in a 50mL reactor and react at 180°C for 12h, cool to room temperature, and separate to obtain a precipitate; S3. Wash the precipitate with pure water 3 times, with ethanol 3 times, and dry it in an oven at 60°C overnight to obtain (ZnCdAgIn) x S.

[0217] The above compounds were prepared into 3 mg mL -1 The solution was coated on the ITO electrode and dried, and then placed in Tris-HCl buffer (pH=7.4) containing ascorbic acid (AA) to form a three-electrode system, with Tris-HCl buffer containing 0.1 M ascorbic acid (AA) as the electrolyte, the platinum electrode as the counter electrode, and the silver-silver chloride electrode as the reference electrode. The light response current was tested in the same way as above, and the results are as follows: Figure 7 shown.

[0218] from Figure 7 It can be seen that with the increase of metal elements, the photocurrent signal gradually increases, proving that there is a synergistic effect among the five metals. Due to the unique cocktail effect, the high entropy material has a significant photocurrent signal.

[0219] Figure 8 It is a flake high entropy sulfide (CdZnCoAgIn) x S was used as a photoactive material to detect the feasibility of kanamycin;

[0220] Specifically, Figure 8 a in A is the method in Example 3, 20 μL, 3 mg mL -1 The flake high entropy sulfide solution is coated on the surface of the electrode (ITO electrode) and dried to form a modified electrode (CdZnCoAgIn) x S / ITO electrode; testing its photocurrent signal (a) and electrochemical impedance spectroscopy (eI) in Tris-HCl buffer (pH = 7.4) containing ascorbic acid (AA) Figure 8 a) in B; b) according to the method in Example 3, polymethacrylate sodium salt solution (PAA, 0.15wt%) and EDC-NHS mixed solution were added dropwise to (CdZnCoAgIn) xOn the S / ITO electrode (incubated after each drop, washed with PBS buffer), (CdZnCoAgIn) was obtained x The photocurrent signal (b) and electrochemical impedance spectroscopy (EIS) of the S / PAA / EDC / NHS / ITO electrode in Tris-HCl buffer (pH=7.4) containing ascorbic acid (AA) were tested. Figure 8 b) in B; c) according to the method in Example 3, 20 μL of cDNA solution was added dropwise to (CdZnCoAgIn) x The S / PAA / EDC / NHS / ITO electrode surface was incubated at 4°C for 12 h, and the electrode was washed with PBS buffer (pH = 7.4) to obtain (CdZnCoAgIn) x The photocurrent signal (c) and electrochemical impedance spectroscopy (EIS) of the S / PAA / EDC / NHS / cDNA / ITO electrode in Tris-HCl buffer (pH=7.4) containing ascorbic acid (AA) were tested. Figure 8 c) in B; d) according to the method in Example 3, 20 μL of BSA solution was added dropwise to (CdZnCoAgIn) x The S / PAA / EDC / NHS / cDNA / ITO electrode surface was incubated at 4°C for 1 h, and the electrode was washed with PBS buffer (pH = 7.4) to obtain (CdZnCoAgIn) x The photocurrent signal (d) and electrochemical impedance spectroscopy (EES) of the S / PAA / EDC / NHS / cDNA / BSA / ITO electrode in Tris-HCl buffer (pH=7.4) containing ascorbic acid (AA) were tested. Figure 8 B d); e is according to the method in Example 3, 20 μL of aptamer Apt solution was added dropwise to (CdZnCoAgIn) x The S / PAA / EDC / NHS / cDNA / BSA / ITO electrode surface was incubated at 37°C for 1 h, and the electrode was washed with PBS buffer (pH = 7.4) to obtain (CdZnCoAgIn) x The photocurrent signal (e) and electrochemical impedance spectroscopy (EIS) of the S / PAA / EDC / NHS / cDNA / BSA / Apt / ITO electrode in Tris-HCl buffer (pH=7.4) containing ascorbic acid (AA) were tested. Figure 8 e) in B; f) according to the method in Example 3, 20 μL of SA-FeY solution was added dropwise to (CdZnCoAgIn) x The S / PAA / EDC / NHS / cDNA / BSA / Apt / ITO electrode surface was incubated at 37°C for 1 h, and the electrode was washed with PBS buffer (pH = 7.4) to obtain (CdZnCoAgIn) xThe photocurrent signal (f) and electrochemical impedance spectroscopy (EIS) of the S / PAA / EDC / NHS / cDNA / BSA / Apt / FeY / ITO electrode in Tris-HCl buffer (pH=7.4) containing ascorbic acid (AA) were tested. Figure 8 f) in B; g) according to the method in Example 4, 20 μL kanamycin (10 ng mL -1 ) solution was added dropwise to (CdZnCoAgIn) x The S / PAA / EDC / NHS / cDNA / BSA / Apt / FeY / ITO electrode surface was incubated at 37°C for 1 h, and the electrode was washed with PBS buffer (pH = 7.4) to obtain (CdZnCoAgIn) x The photocurrent signal (f) and electrochemical impedance spectroscopy (EIS) of the S / PAA / EDC / NHS / cDNA / BSA / Apt / FeY / kanamycin / ITO electrode in Tris-HCl buffer (pH=7.4) containing ascorbic acid (AA) were tested. Figure 8 f) in B; h is the method in Example 4, adding dopamine (DA) solution dropwise to (CdZnCoAgIn) x The S / PAA / EDC / NHS / cDNA / BSA / Apt / FeY / ITO electrode surface was incubated at 37°C for 0.5 h, and the electrode was washed with PBS buffer (pH = 7.4) to obtain (CdZnCoAgIn) x The photocurrent signal (h) and electrochemical impedance spectroscopy (EIS) of the S / PAA / EDC / NHS / cDNA / BSA / Apt / FeY / DA / ITO electrode in Tris-HCl buffer (pH=7.4) containing ascorbic acid (AA) were tested. Figure 8 h in B).

[0221] from Figure 8 In A, we can see that the high entropy sulfide (CdZnCoAgIn) is a flake-like x S was used as a photoactive material to detect the feasibility of kanamycin. Initially, (CdZnCoAgIn) xThe S / ITO electrode shows a large photocurrent signal (a). In order to activate the electrode, the electrode surface is treated with PAA and NHS / EDC (b). Then, the cDNA complementary to the kanamycin aptamer is successfully fixed on the electrode surface, and the photocurrent signal weakens (c). After BSA blocks the nonspecific active sites on the surface (d), the kanamycin aptamer is introduced and complementary to the cDNA chain on the electrode (e). After the FeY nanozyme is modified, the photocurrent decreases (f). 10 ng mL-1 of kanamycin is introduced into the electrode, allowing the aptamer modified with the FeY nanozyme to escape the electrode surface, and the anode signal is restored (g). Finally, DA is dropped on the electrode surface to switch the cathode signal (h).

[0222] Figure 8 Similar results can be seen in B. During the step-by-step construction process, the interfacial charge transfer resistance of the electrode generally increased, which was mainly due to the reagents used hindering the transfer of electrons. After DA treatment, the resistance value decreased, which may be due to the fact that PDA changed the electrochemical properties of the electrode.

[0223] Fig. 9 The photoelectrochemical sensing analysis of kanamycin is as follows. Specifically, according to the method in Examples 3 to 4, the detection of different kanamycin concentrations (1 pg mL -1 To 10 ng mL -1 ) of the test solution, and the cathode photoresponse current signal of the electrode;

[0224] in, Fig. 9 A is different kanamycin concentrations (1pg mL -1 To 10 ng mL -1 ) of the test solution, Fig. 9 B is different kanamycin concentrations (1pg mL -1 To 10 ng mL -1 ) of the test solution, Fig. 9 C is different kanamycin concentrations (1pg mL -1 To 10 ng mL -1 ) of the test solution, Fig. 9 D is different kanamycin concentrations (1pg mL -1 To 10 ng mL -1 ) is related to the ratio of the difference between the anodic photoresponse current signal and the cathodic photoresponse current signal of the test solution and the kanamycin concentration.

[0225] Fig. 9 The kanamycin concentration corresponding to a is 1 pg mL -1The kanamycin concentration corresponding to b is 5 pg mL -1 The kanamycin concentration corresponding to c is 10 pg mL -1 , d corresponds to a kanamycin concentration of 50 pg mL -1 The corresponding kanamycin concentration is 100 pg mL -1 The corresponding kanamycin concentration is 500 pg mL -1 The kanamycin concentration corresponding to g is 1 ng mL -1 The kanamycin concentration corresponding to h is 5 ng mL -1 The kanamycin concentration corresponding to i is 10 ng mL -1 .

[0226] Fig. 9 As shown in A, with the increase of kanamycin concentration, the photocurrent signal gradually recovered.

[0227] Fig. 9 As shown in B, as the kanamycin concentration increases, the photocurrent signal switches to the cathode signal and gradually decreases.

[0228] Fig. 9 As shown in C, Figure 7 The combination of A and 7B can more intuitively show the signal change of photocurrent.

[0229] like Fig. 9 As shown in D, when the kanamycin concentration range is 1pg mL -1 To 10 ng mL -1 These results indicate that the high entropy sulfide (CdZnCoAgIn) based on the x The photoelectrochemical sensor of S was feasible in the determination of kanamycin.

[0230] Fig.10 A is the flake high entropy sulfide (CdZnCoAgIn) verified by selective testing x Specificity of S;

[0231] like Fig.10 As shown in A, from left to right are chloramphenicol (Chloramphenicol), amoxicillin (AMOX), tetracycline hydrochloride (TET), streptomycin (Streptomycin), oxytetracycline (Oxytetracycline), mixture (Mixture), kanamycin (KAN); the six antibiotics were prepared into 10 ng ml -1 The test solution is obtained according to the method in Example 4, and the anode light response current signal difference and the cathode light response current signal difference corresponding to the test solution of different antibiotics are obtained. The results are as follows Fig.10 As shown in A; Fig.10 Mix means that six antibiotics, namely, chloramphenicol, amoxicillin (AMOX), tetracycline hydrochloride (TET), streptomycin (Streptomycin), oxytetracycline (Oxytetracycline), and kanamycin (KAN), are mixed to obtain a mixed test solution, and the concentration of each antibiotic in the mixed test solution is 10 ng ml -1 According to the method in Example 4, the anode light response current signal difference and the cathode light response current signal difference corresponding to the test solution of different antibiotics are obtained. The results are as follows Fig.10 As shown in A;

[0232] Fig.10 B contains 10 ng ml -1 The kanamycin solution to be tested is tested according to the method in Example 4, and the cathode light response current signal changes with time.

[0233] from Fig.10 As can be seen from A, the flaky high entropy sulfide (CdZnCoAgIn) of the present invention x The photoelectrochemical sensor with S as the photoactive material is specific to kanamycin; Fig.10 As can be seen in B, the invented high entropy sulfide (CdZnCoAgIn) x The photoelectrochemical sensor with S as the photoactive material has good stability.

[0234] By changing the flake high entropy sulfide (CdZnCoAgIn) x The concentration of S is 3 mg mL -1 When the flaky high entropy sulfide (CdZnCoAgIn) x The photocurrent signal of S reaches the highest, therefore, the flake high entropy sulfide (CdZnCoAgIn) x The optimal concentration of S was 3 mg mL -1 ; The incubation time was set to 30 min. By changing the concentration of DA, when the concentration of DA was 500 mM, the switched cathode signal reached the lowest. Therefore, the optimal concentration of DA was 500 mM.

[0235] Fig.11 The flaky high entropy sulfide (CdZnCoAgIn) prepared in Example 1 x S is formulated as 3 mg mL -1The solution was coated on the ITO electrode and dried, and then placed in a Tris-HCl buffer (pH=7.4) containing ascorbic acid (AA) to form a three-electrode system. The Tris-HCl buffer containing 0.1 M ascorbic acid (AA) was used as the electrolyte. The photocurrent signals at different times were tested in the same manner as above.

[0236] like Fig.11 As shown, the flake high entropy sulfide (CdZnCoAgIn) x As time goes by, the photocurrent signal remains stable and basically remains at a certain level, indicating that the flake high entropy sulfide (CdZnCoAgIn) x S has good reproducibility.

[0237] According to Examples 1 to 4, the present invention based on the sheet-like high entropy sulfide (CdZnCoAgIn) x S's kanamycin photoelectric analysis method is not only suitable for actual sample detection, but also has low detection limit, excellent selectivity and reliability. In addition, the method is easy to operate, saving time and cost.

[0238] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing flaky high entropy sulfide, characterized in that: The following steps are involved: Dissolving Cd salt, Zn salt, Co salt, Ag salt, In salt and thioacetamide in water to obtain a mixture; The mixture is placed in a reactor for reaction, and a precipitate is obtained by separation; The precipitate is washed and dried to obtain flaky high entropy sulfide.

2. The method for preparing flaky high entropy sulfide according to claim 1, characterized in that: The Cd salt includes at least one of Cd(CH3COO)2, CdCl2, and Cd(NO3)2; And / or, the Zn salt includes at least one of Zn(CH3COO)2, Zn(NO3)2, ZnSO4, and ZnCl2; And / or, the Co salt includes at least one of Co(CH3COO)2, Co(NO3)2, CoSO4, and CoCl2; And / or, the Ag salt includes at least one of AgCH3COO and AgNO3; And / or, the In salt includes at least one of In(NO3)3, InCl3, In2(SO4)3, and In(CH3COO)3; And / or, the molar ratio of the Cd salt, Zn salt, Co salt, Ag salt, In salt and thioacetamide is (1-1.2):(1-1.2):(1-1.2):(1-1.2):(1-1.2):(1-1.2); The molar volume ratio of the Co salt to the water is (1-1.2) mmol: (35-40) mL; And / or, the reaction temperature is 180-190° C., and the reaction time is 12-15 hours.

3. A flaky high entropy sulfide, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 2.

4. A method for preparing a nanozyme, characterized in that: The following steps are involved: Dissolve Zn salt and 2-methylimidazole in methanol respectively, mix and stir, let stand, and separate to obtain a precipitate; The precipitate, Fe salt and Y salt are added into methanol, heated and evaporated to dryness, and the nanomaterial is separated; calcining the nanomaterial under an inert atmosphere to obtain a calcined product; The calcined product is dissolved in dilute sulfuric acid and etched to separate the nanozyme.

5. The method for preparing the nanozyme according to claim 4, characterized in that: The Fe salt is Fe(ACAC)3; And / or, the Y salt is Y(ACAC)3; And / or, the Zn salt includes at least one of Zn(CH3COO)2, Zn(NO3)2, ZnSO4, and ZnCl2; and / or, dissolving Zn salt and 2-methylimidazole in methanol respectively, stirring at 20-25° C. for 10-20 min, standing for 12-15 h, washing with methanol and separating to obtain a precipitate; wherein the molar ratio of Zn salt to 2-methylimidazole is (0.04-0.05):(0.16-0.20), and the molar volume ratio of Zn salt to methanol is (0.04-0.05) mol:(200-400) mL; And / or, adding the precipitate and the Fe salt and the Y salt to methanol, heating at 80-90° C. to evaporate the methanol, and separating to obtain the nanomaterial; wherein the mass ratio of the precipitate to the Fe salt and the Y salt is (1-1.2):(0.025-0.03):(0.025-0.03), and the mass volume ratio of the Fe salt to the methanol is (0.025-0.03) g:(50-100) mL; And / or, calcining the nanomaterial under an inert atmosphere to obtain a calcined product, specifically comprising: heating the nanomaterial under an inert atmosphere from room temperature to 800-900° C. at a rate of 5-6° C. / min, calcining for 2-3 hours, and then cooling to room temperature to obtain a calcined product; The inert atmosphere includes at least one of nitrogen, helium, neon and argon; And / or, in the step of dissolving the calcined product in dilute sulfuric acid for etching, the etching comprises: placing the calcined product in dilute sulfuric acid, etching at 20-25° C. for 10-15 hours, and the concentration of the dilute sulfuric acid is 0.5-1M.

6. Use of the flaky high entropy sulfide prepared by the preparation method according to any one of claims 1 to 2 or the flaky high entropy sulfide according to claim 3 in detecting the concentration of kanamycin.

7. A biosensor, characterized in that: The method for constructing the biosensor comprises the following steps: S1. coating the flaky high entropy sulfide according to claim 3 on the surface of an electrode and drying the flaky high entropy sulfide to form a modified electrode; S2, dropping polymethacrylate sodium salt solution on the surface of the modified electrode, incubating, and washing the electrode with PBS buffer; S3, drop the EDC-NHS mixed solution onto the electrode surface in S2, incubate, and wash the electrode with PBS buffer; S4, drop the cDNA solution onto the electrode surface in S3, incubate, and wash the electrode with PBS buffer; S5, drop the BSA solution onto the electrode surface in S4, incubate, and wash the electrode with PBS buffer; S6, adding the aptamer Apt solution dropwise to the electrode surface in S5, incubating, and washing the electrode with PBS buffer; S7, dropping the SA-FeY solution onto the electrode surface in S6, incubating, and washing the electrode with PBS buffer to obtain a biosensor; Wherein, the gene sequence of the cDNA is 5'-GTCGGCTTAGCCTCAACCCCCA-3'; The gene sequence of the aptamer Apt is 5'-TGGGGGTTGAGGCTA AGCCGAC-3'; The preparation method of the SA-FeY solution is: Adding the nanozyme prepared by the preparation method according to any one of claims 4 to 5 into water to obtain a nanozyme solution; The streptavidin solution and the nanozyme solution were mixed, the supernatant was removed by centrifugation, and the precipitate was collected; PBS buffer was added to the precipitate to obtain a SA-FeY solution.

8. The biosensor according to claim 7, wherein The method for constructing the biosensor comprises the following steps: S1. Add the flaky high entropy sulfide into water to obtain 3-4 mg mL -1 The flaky high entropy sulfide solution is coated on the electrode surface and dried to form a modified electrode; S2, dripping polymethacrylate sodium salt solution onto the surface of the modified electrode, incubating at 36-37°C for 0.5-1h, and washing the electrode with PBS buffer; the mass concentration of the polymethacrylate sodium salt solution is 0.15-0.2%; S3, dripping the EDC-NHS mixed solution onto the electrode surface in S2, incubating at 4-5°C for 1-2h, and washing the electrode with PBS buffer; the preparation method of the EDC-NHS mixed solution is as follows: adding EDC and NHS into PBS buffer to obtain an EDC-NHS mixed solution, wherein the concentration of EDC is 10-12mM, and the concentration of NHS is 2-4mM; S4, dropping the cDNA solution onto the electrode surface in S3, incubating at 4-5°C for 12-15h, and washing the electrode with PBS buffer; the preparation method of the cDNA solution is: adding cDNA to PBS buffer to obtain a cDNA solution, wherein the concentration of the cDNA solution is 1.0-1.2 μM; S5, dropping a BSA solution onto the electrode surface in S4, incubating at 4-5°C for 1-2 hours, and washing the electrode with a PBS buffer solution; the BSA solution is prepared by adding BSA to a PBS buffer solution to obtain a BSA solution; the mass concentration of the BSA solution is 1.0-2.0%; S6, adding the aptamer Apt solution dropwise to the electrode surface in S5, incubating at 36-37° C. for 1-2 hours, and washing the electrode with PBS buffer; the preparation method of the aptamer Apt solution is: adding the aptamer Apt to the PBS buffer to obtain the aptamer Apt solution, wherein the concentration of the aptamer Apt solution is 1.0-1.2 μM; S7, dropping the SA-FeY solution onto the electrode surface in S6, incubating at 36-37°C for 1-2h, and washing the electrode with PBS buffer to obtain a biosensor; The concentration of the streptavidin solution is 1 to 2 mg / mL, and the concentration of the nanozyme solution is 1 to 2 mg / mL; The streptavidin solution and the nanozyme solution are mixed, the supernatant is removed by centrifugation, and the precipitate is collected; in the step of adding PBS buffer to the precipitate, the volume ratio of the streptavidin solution, the nanozyme solution, and the PBS buffer solution is (200-220):(400-420):(600-620); The pH of the PBS buffer is 7.4-7.

5.

9. A method for detecting kanamycin concentration, characterized in that: The following steps are involved: S1. Provide a biosensor as claimed in any one of claims 7 to 8, drop a kanamycin test solution onto the electrode surface of the biosensor, incubate at 36 to 37° C. for 1 to 2 h, and wash the electrode with PBS buffer; S2, placing the electrode in a Tris-HCl buffer containing ascorbic acid, and detecting the anode photoresponse current signal of the electrode when the concentration of natamycin is zero and at the current concentration; The anode light response current signal value of the electrode at the current concentration is subtracted from the anode light response current signal value of the electrode when the napromycin concentration is zero, to obtain the anode light response current signal difference; S3, add dopamine solution to the electrode surface in S2, incubate at 36-37°C for 0.5-1h, and wash the electrode with PBS buffer; S4, placing the electrode in S3 in a Tris-HCl buffer containing ascorbic acid, and detecting the cathode photoresponse current signal of the electrode when the concentration of natamycin is zero and at the current concentration; The cathode light response current signal value of the electrode at the current concentration is subtracted from the cathode light response current signal value of the electrode when the namycin concentration is zero, to obtain the cathode light response current signal difference; S5. Detect the kanamycin concentration according to the ratio of the difference of the anode light response current signal to the cathode light response current signal.

10. The method for detecting kanamycin concentration according to claim 9, characterized in that: The pH of the Tris-HCl buffer is 7.4-7.5, and the concentration of ascorbic acid in the Tris-HCl buffer is 0.1-0.2 M; The method for preparing the dopamine solution is as follows: dopamine is added into water to obtain the dopamine solution; the concentration of the dopamine solution is 500-600 mM.